ANALYSIS OF THE INFLUENCE OF MESH SURFACES ON THE CLEANING PROCESS IN THE PROCESS OF RECYCLING SEEDED COTTON (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article provides information about mesh surfaces, which are the main  element of seed cleaning equipment, analyzes information about the designs of mesh  surfaces and their mesh geometric shapes and their application in the technological  process, and gives recommendations